Foundations & principles of distributed manufacturing : elements of manufacturing networks, cyber-physical production systems and smart automation /: elements of manufacturing networks, cyber-physical production systems and smart automation. (2015) - Kühnle, H (Hermann); Bitsch, Günter, 1963-
No abstract available